Bangladesh road to sustainable development : people's voice - People's Consultation on Sustainable Development: National Assessment Report for WSSD, Bangladesh (2002 : Forum of Environmental Journalists of Bangladesh); Chowdhury, Quamrul Islam; Forum of Environmental Journalists of Bangladesh (Dhaka : Forum of Environmental Journalists of Bangladesh, 2002)
Contributed articles presented at the People's Consultation on Sustainable Development: National Assessment Report for WSSD, Bangladesh conducted by Forum of Environmental Journalists of Bangladesh at six administrative divisional headquaters of Bangladesh between 19th Feb. to 10th March, 2002.
committed to retain
Keywords: Sustainable development -- Bangladesh -- Congresses; Sustainable development; Bangladesh; Conference papers and proceedings